Radiation interception and rain water use efficiency in cotton based intercropping - Venkataraman, N.S; Ragavan, T.; Saravanan, T. (GEORGIKON FOR AGRICULTURE, 2008)
Field experiment was conducted on crop diversification in cotton based vegetable intercropping at Agricultural Research Station, Kovilpatti Tamil Nadu, India during the monsoon season 2005-06 in randomized block design with three replications. In this investigation, productivity, radiation and rain water use efficiency of cotton intercropped with vegetables were tried in rainfed vertisol condition. The highest cotton equivalent yield was obtained from cotton + radish intercropping followed by cotton + onion. The rain water utilization efficiency for that combination was 1.98 and 1.93 kg ha–1 mm-1. Substitution of cotton with short duration vegetables intercrops found more beneficial.